Kształtowanie relacji z klientami w wybranych firmach Podkarpacia - Marcinek, Anna; Rogoż, Alicja; Sieniawska, Krystyna (Forming Relations with Customers in Chosen Companies of Podkarpackie Province, 2006)
The article presents considerations relating to forming relations with customers in two companies. The role of personnel has been shown in strengthening the ties with customers and the importance of pro-loyality actions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 531-538